Design, synthesis and anticancer evaluation of chalcone derivatives of oxazol-4-yl)-2-morpholinothiazole as anticancer agents - Muralidhar Reddy Rachala; Thirumala Chary Maringanti; Laxminarayana Eppakayala (Results in Chemistry, 2023)
A new library of chalcone derivatives of oxazol-4-yl)-2-morpholinothiazole (10a-j) have been developed and synthesized. All these synthesized compounds were firmed by 1H NMR, 13C NMR and mass spectral data. Further, the in vitro anticancer effects of newly derived compounds (10a-j) were investigated towards four human cancer cell lines including PC3 and DU-145 (prostate cancer), A549 (lung cancer) & MCF-7 (breast cancer) through MTT assay, and was compared with etoposide which is positive control. Most of the evaluated compounds displayed excellent to moderate activities than etoposide. Among all, compounds 10a, 10b, 10c, 10d, 10e and 10f exhibited more potent activity. Predominantly, one compound 10d displayed superior anticancer activity.